Future NATO adapting to new realities - Olsen, John Andreas (Whitehall paper, 2020)
Future NATO looks at the challenges facing NATO in the 21stcentury and examines how the Alliance can adapt to ensure its continued success For more than 70 years, the North Atlantic Alliance has helped to preserve peace and stability in the Euro-Atlantic area. It has been able to adjust to varying political and strategic challenges. We must ensure that NATO continues to be effective in the future. This requires looking ahead, challenging habitual approaches, exchanging ideas, and advancing new thinking. I highly recommend Future NATO to policymakers, military professionals and scholars alike, as it offers necessary critical and constructive analysis of current and future challenges posed to our security and defence. Annegret Kramp-Karrenbauer, Minister of Defence, Germany Since 1949, NATO has successfully upheld common principles and adapted to new realities. As Future NATO examines, the Alliance is facing a new set of external and internal challenges in the decades to come. The Alliance and its partners need to remain committed to future changes. I recommend this excellent study to all, but especially to the younger generation of scholars and future policymakers. Trine Bramsen, Minister of Defence, Denmark Over the last 70 years, Europe has lived in peace and prosperity because of NATO, with unity as our most important weapon. We may have our differences, but we will continue to work on our common cause to promote peace, security and stability. To effectively do so, NATO needs to continuously adapt to changing security situations. An important current challenge is to ensure European Allies take more responsibility for their security. But we also need to look at future challenges and find innovative solutions for them. Future NATO offers a useful analysis that can help us prepare for what is to come for the Alliance.